Exploring rootedness in the very rural Great Plains counties of Kansas and Nebraska - Wetherholt, William A. (Kansas State University, 2016)
The population of the American Great Plains has grown steadily but unevenly. While metropolitan areas − primarily on the peripheries of the Plains − have expanded, significant interior portions have experienced decades of outmigration and the challenges that accompany the exodus. Geographers have explored the interplay between rural population loss and service consolidation, the many reasons people leave, the age-specific dynamics of those leaving, and the varied strategies being employed at different scales to coax people back. The vantage point of the residents who remain in emptying spaces has received little attention, however. Grounded theory guided a sequential mixed method approach to gain a better perspective on the aspects of place that contribute to an individual’s rootedness in the most rural and depopulating portions of the central Great Plains. Questionnaires were mailed in 2015 to 1,000 randomly-sampled households in ten counties of Kansas and Nebraska. Counties were selected on the most rural USDA ERS Rural-Urban Continuum and Urban-Influence Codes, ERS typology identifying population loss, and the most geographically-remote USDA Frontier and Remote Area designation. Focus groups were conducted after the mailed questionnaires in the county seats of three of counties that received the mailed survey. Correlation and contingency analyses were used to explore relationships within the closed-ended questionnaire responses for statistical significance. Open-ended responses provided depth to the closed-ended material. Results of the focus groups provided rich qualitative data that triangulated with quantitative results and offered a holistic view of the aspects of place encouraging someone to remain in a depopulating region. The elements of place encouraging rootedness were similar between the responses on the mailed questionnaire and those from the participants in the three focus groups. Rootedness was most associated with a sense of belonging. Rooted respondents also indicated that they felt good about where they live. In addition, many rooted individuals perceive themselves to be insiders in the community and view community spirit to be strong. Questionnaire results suggest that being involved with the community had a positive relationship with levels of rootedness. Rooted respondents were also more likely to perceive the visual appearance of their nearby surroundings favorably. A significant concern was the need for more vocational services within the focal study counties. A lack of sufficient trained individuals was seen as a reflection of institutional fast-tracking of students out of the area combined with a lack of support for motivating young people to apply their skills locally. Communities within the study area are not in danger of disappearing anytime soon, but their populations’ continued downward trajectory undermines their viability over the long term. Strategies like a shift in local educational approaches and inclusive activities aimed at those more likely to leave may encourage new roots to be put down or nurture roots to grow deeper, thus helping to curb outmigration.
Keywords: Place attachment; Rural geography; Population geography; Outmigration; Great Plains; Qualitative and mixed methods